Research interest on dental sealant in dentistry based on the 100 most cited articles: bibliometric analysis - Melissa Santos da Silva SIMÕES; Aurélio de Oliveira ROCHA; Mariana Perini ZENDRON; Pablo Silveira SANTOS; Michele BOLAN; Carla Miranda SANTANA; Mariane CARDOSO (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract The aim of this study was to identify and analyze the characteristics of the 100 most cited articles about dental sealants (DS) in dentistry. In September 2023, a search was performed in the Web of Science Core Collection (WoS-CC) database. The following information was extracted from each article: number and density of citations, year of publication, authorship, journal, impact factor, keywords, study design, theme, continent, country, and institution. The citations of the WoS-CC were compared with those of the Scopus and Google Scholar databases. The VOSviewer software was used to generate collaborative networks. The number of citations ranged from 33 to 205. The articles were published between 1961 and 2016. Buonocore MG (7%) was the most prominent author among the most cited. The Journal of the American Dental Association was the most frequent journal (25%) and Journal of Dental Research (7.6) had the highest impact factor. Most studies had interventional (41%) and laboratory (31%) designs, mainly addressing DS effectiveness in the prevention and control of dental caries (86%). There was a predominance of publications from North America (46%) and the USA was the country with the highest number of articles (44%). The most frequent institutions were the Centers for Disease Control and Prevention (USA) and the University of Rochester (USA) (6% each). "Retention" was the most frequent keyword. In conclusion, the 100 most cited articles were mostly interventional and laboratory studies, addressing the retention and efficacy of DS. Most of the articles were concentrated in North America and Europe, demonstrating a little collaboration from other continents.